Buying and Selling Risk - An Experiment Investigating Evaluation Asymmetries - Werner Güth; Matteo Ploner; Ivan Soraperra (Center for Economic Studies and ifo Institute (CESifo), 2014)
Experimental studies of the WTP-WTA gap avoid social trading by implementing an incentive compatible mechanism for each individual trader. We compare a traditional random price mechanism and a novel elicitation mechanism preserving social trading, without sacrificing mutual incentive compatibility. Furthermore, we focus on risky goods - binary monetary lotteries - for which asymmetries in evaluations are more robust with respect to experimental procedures. For both elicitation mechanisms, the usual asymmetry in evaluation by sellers and buyers is observed. An econometric estimation sheds new light on its causes: potential buyers are over-pessimistic and systematically underweight the probability of a good outcome.
Keywords: D81; 330; WTP-WTA gap; risk; elicitation mechanisms; probability weighting